2010
DOI: 10.1177/1066896910367649
|View full text |Cite
|
Sign up to set email alerts
|

Low-Grade Cribriform Cystadenocarcinoma of the Parotid Gland: A Neoplasm With Favorable Prognosis, Distinct From Salivary Duct Carcinoma

Abstract: Low-grade cribriform cystadenocarcinoma of salivary glands is a recently described rare tumor with favorable prognosis. This study reports the case of 50-year-old woman with swelling lasting for 9 months in the right parotideomasseteric area. Grossly, the tumor was well circumscribed and dominated by cystic space. Microscopically, the neoplasm consisted of well-demarcated islets, some of them cystically dilated. The architecture of islets varied from solid to cribriform and micropapillary without comedo-type n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 14 publications
0
33
0
1
Order By: Relevance
“…Delgado et al [1] detailed many salient similarities and differences between LG-SDC and conventional SDC and concluded ''that LG-SDC represents the low grade end of the spectrum of salivary duct neoplasms''. LG-SDC and conventional SDC are composed of neoplastic cells with ductal phenotype and varying degree of apocrine differentiation and AR expression [1,6,14,31,41] but exhibit significant clinicopathologic differences including the expression of S100 protein, with 84 % of LG-SDCs positive for S100 protein. In contrast, the data regarding S100 protein expression in conventional SDC is more controversial with Lewis et al [30] reporting expression in only 4 % while Brandwein et al [42] reported reaction in 100 % of cases.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Delgado et al [1] detailed many salient similarities and differences between LG-SDC and conventional SDC and concluded ''that LG-SDC represents the low grade end of the spectrum of salivary duct neoplasms''. LG-SDC and conventional SDC are composed of neoplastic cells with ductal phenotype and varying degree of apocrine differentiation and AR expression [1,6,14,31,41] but exhibit significant clinicopathologic differences including the expression of S100 protein, with 84 % of LG-SDCs positive for S100 protein. In contrast, the data regarding S100 protein expression in conventional SDC is more controversial with Lewis et al [30] reporting expression in only 4 % while Brandwein et al [42] reported reaction in 100 % of cases.…”
Section: Discussionmentioning
confidence: 99%
“…In tumors with areas of invasion, this myoepithelial layer appeared discontinuous [4]. Cytokeratin 5/6 (CK5/6) also highlighted myoepithelial cells in one additional case [6].…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 3 more Smart Citations